Effects of Debris on Bridge Pier Scour - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 653: Effects of Debris on Bridge Pier Scour explores guidelines to help estimate the quantity of accumulated, flow event debris, based on the density and type of woody vegetation and river bank condition upstream and analytical procedures to quantify the effects of resulting debris-induced scour on bridge piers.The debris photographic archive, the survey questionnaire and list of respondents, and the report on the field pilot study related to development of NCHRP 653 was published as NCHRP Web-Only Document 148: Debris Photographic Archive and Supplemental Materials for NCHRP Report 653.
Keywords: Transportation and Infrastructure

Countermeasures to Protect Bridge Piers from Scour - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 593: Countermeasures to Protect Bridge Piers from Scour explores practical selection criteria for bridge-pier scour countermeasures; guidelines and specifications for the design and construction of those countermeasures; and guidelines for their inspection, maintenance, and performance evaluation. Produced along with the report is an interactive version of the countermeasure selection methodology, which defines the proper conditions for the use of each specific countermeasure, and a reference document that contains detailed laboratory testing results and translations of three German "Code of Practice" documents.There is a summary document, Paths to Practice, available.
Keywords: Transportation and Infrastructure

Innovative Bridge Designs for Rapid Renewal - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-R04-RR-1: Innovative Bridge Designs for Rapid Renewal documents the development of standardized approaches to designing and constructing complete bridge systems for rapid renewal.The report also describes a demonstration project on US-6 over Keg Creek near Council Bluffs, Iowa, that was completed in 2011 using the accelerated bridge construction standards developed as part of Renewal Project R04.The following three videos were also produced related to the Keg Creek project:• ABC for Everyday Bridges (18:39) highlights the specific techniques used to deliver a new bridge with only a 10-day closure.• One Design—10,000 Bridges (9:46) describes a tool kit for designing and constructing bridges that brings home the benefits of accelerated bridge construction techniques so local contractors can use typical equipment to build bridges quickly and efficiently.• Time-Lapse Video (1:30) shows accelerated bridge construction techniques being used by a local contractor with standard equipment to replace the Keg Creek three-span bridge.SHRP 2 Renewal Project R04 also developed an Innovative Designs for Rapid Renewal: ABC Toolkit that describes standardized approaches to designing and constructing complete bridge systems for rapid renewals, as well as a case study on the accelerated bridge construction techniques used in the I-84 bridge project in New York. In addition, the project developed a half- and full-day presentations to help facilitate training on the accelerated bridge process to interested parties. In June 2013, SHRP 2 released a Project Brief on Renewal Project R04.​Software Disclaimer: This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Evaluation of Bridge Scour Research: Pier Scour Processes and Predictions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 175: Evaluation of Bridge Scour Research: Pier Scour Processes and Predictions explores the current state of knowledge regarding bridge-pier scour, assesses several methods for design estimates of scour depth, examines a structured methodology for scour-depth estimation for design purposes, and highlights aspects of pier-scour in need of potential further research.In September 2012 TRB released NCHRP Research Results Digest 378: Evaluation of Bridge Scour Research, which summarizes key finding of NCHRP Web-Only Document 175 along with two other NCHRP projects that explored processes and predictions related to pier scour, abutment and contraction scour, and geomorphic scour.
Keywords: Transportation and Infrastructure

Designing Safety Regulations for High-Hazard Industries - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB Special Report 324: Designing Safety Regulations for High-Hazard Industries, examines key factors relevant to government safety regulators when choosing among regulatory design types, particularly for preventing low-frequency, high consequence events. In such contexts, safety regulations are often scrutinized after an incident, but their effectiveness can be inherently difficult to assess when their main purpose is to reduce catastrophic failures that are rare to begin with. Nevertheless, regulators of high-hazard industries must have reasoned basis for making their regulatory design choices.Asked to compare the advantages and disadvantages of so-called “prescriptive” and “performance-based” regulatory designs, the study committee explains how these labels are often used in an inconsistent and misleading manner that can obfuscate regulatory choices and hinder the ability of regulators to justify their choices. The report focuses instead on whether a regulation requires the use of a means or the attainment of some ends—and whether it targets individual components of a larger problem (micro-level) or directs attention to that larger problem itself (macro-level). On the basis of these salient features of any regulation, four main types of regulatory design are identified, and the rationale for and challenges associated with each are examined under different high-hazard applications.Informed by academic research and by insights from case studies of the regulatory regimes of four countries governing two high-hazard industries, the report concludes that too much emphasis is placed on simplistic lists of generic advantages and disadvantages of regulatory design types. The report explains how a safety regulator will want to choose a regulatory design, or combination of designs, suited to the nature of the problem, characteristics of the regulated industry, and the regulator’s own capacity to promote and enforce compliance. This explanation, along with the regulatory design concepts offered in this report, is intended to help regulators of high-hazard industries make better informed and articulated regulatory design choices.Accompanying the report, a two-page summary provides a condensed version of the findings from this report.
Keywords: Transportation and Infrastructure

Evaluation of Bridge Scour Research: Geomorphic Processes and Predictions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 177: Evaluation of Bridge Scour Research: Geomorphic Processes and Predictions explores the impact of long-term aggradation and degradation, and lateral river channel migration, on highway structures.In September 2012 TRB released NCHRP Research Results Digest 378: Evaluation of Bridge Scour Research, which summarizes key finding of NCHRP Web-Only Document 177 along with two other NCHRP projects that explored processes and predictions related to pier scour, abutment and contraction scour, and geomorphic scour.
Keywords: Transportation and Infrastructure

Post-Extreme Event Damage Assessment and Response for Highway Bridges - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 497: Post-Extreme Event Damage Assessment and Response for Highway Bridges reviews the procedures that state departments of transportation and two local authorities, New York City and Los Angeles County, use to assess the damage in bridges in response to extreme events and conduct emergency response activities. Extreme events include those with geological sources (such as earthquakes and landslides), from hydro-meteorological sources (such as hurricanes and floods), or those of man-made origin, either accidental (such as truck crashes) or malicious (such as terrorist attacks).
Keywords: Transportation and Infrastructure

Countermeasures to Protect Bridge Abutments from Scour - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB's National Cooperative Highway Research Program (NCHRP) Report 587: Countermeasures to Protect Bridge Abutments from Scour examines selection criteria and guidelines for the design and construction of countermeasures to protect bridge abutments and approach embankments from scour damage. The report explores two common forms of bridge abutments--wing-wall (vertical face with angled walls into the bank) and spill-through (angled face).
Keywords: Transportation and Infrastructure

Guidelines for Shielding Bridge Piers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Report 892: Guidelines for Shielding Bridge Piers provides proposed load and resistance factor design (LRFD) bridge design pier protection specifications and proposed occupant protection guidelines. Bridge piers are generally close to the roadway to minimize bridge lengths. As a consequence, barriers are normally placed around piers to reduce the potential of vehicle crashes damaging the piers. However, the design and placement of the barriers may not have taken into consideration the possibility that vehicles, particularly large trucks, might still impact the pier. The report also includes four examples that illustrate the use of the proposed specifications and guidelines for shielding bridge piers.
Keywords: Transportation and Infrastructure

Design Guide for Bridges for Service Life - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-R19A-RW-2: Design Guide for Bridges for Service Life provides information and defines procedures to systematically design new and existing bridges for service life and durability.
Keywords: Transportation and Infrastructure

Ship Collisions with Bridges: The Nature of the Accidents, Their Prevention and Mitigation (The National Academies Press, 1983)